Front-end web development with Modern HTML, CSS, and JavaScript. (Packt Publishing, 2022)
Learn all the core fundamentals of modern web design, covering all the commonly used syntax for HTML and CSS. About This Video Understand how to create elements with code and add them to your web page Learn to select elements from your web page with JavaScript Learn to style your web pages with CSS In Detail JavaScript code runs your browser as your HTML page loads. Adding JavaScript to your code can improve the user experience of the web page. This course will cover the basics of getting started with JavaScript, HTML, and CSS and the code syntax to write JavaScript code. JavaScript is a set of instructions you can add to your code to let the browser know what to do next. It covers the core concepts of JavaScript so that you can try the code and get familiar with what it does. Using JavaScript, you can access the HTML DOM in the browser, which allows you to interact and manipulate web page content. JavaScript creates the interactive and dynamic content seen today on all major modern web pages. Learn what CSS is and how you can style your web pages with Cascading Style Sheets (CSS). HTML provides a structure for your webpage; CSS allows you to style your page. Design the page with your style, set up page layouts, add colors, fonts, and more. Present your webpages as you want them to look, independent of the HTML; you can make your web content look and style as you imagine it should. You will also learn Document Object Model (DOM), which is a programming interface for HTML documents; that is, the logical structure of a page and how the page content can be accessed and manipulated. By the end of the course, you can start coding quickly and focus on designing your interactive and dynamic web pages. Audience This course is for beginners in web design and for anyone who wants to learn more about coding or for anyone curious to learn HTML, CSS, and JavaScript. This course can also be taken by someone who wants to create interactive web pages and who wants a quick and effortless way to start coding.